Experimental analysis and simulation of low-velocity impact damage of composite laminates - Falcó, O.; Lopes, C.S.; Sommer, D.E.; Thomson, D.; Ávila, R.L.; Tijs, B.H.A.H. (Composite structures, 2022)
The capability to accurately analyse the response of multi-directional composite laminates during impact events is of high importance for the design of lightweight aircraft structures. In this work, both experimental and numerical analyses are performed covering a large design-space of laminates for all aspects from on-set of damage and barely visible impact damage up to clearly visible impact damage and full penetration of the laminates. The impact tests are simulated using a sophisticated three-dimensional continuum damage model, combined with an automated meso-scale model generation algorithm for ply-by-ply, material/fibre-aligned meshing of laminated composite coupons. To assess the accuracy of the predictions, an extensive validation test program of several configurations and impact energies has been performed, thus demonstrating that the simulations are capable of accurately predicting the damage and failure mechanisms under low-velocity impact loading. Not only the evolution of impact loads and energy dissipated are numerically analysed, but the competition of the dominant failure mechanisms from low impact energy and full penetration cases are also macroscopically replicated.